Analisis Produktivitas Pada Industri Batik Dengan Konsep Green Productivity(Studi Kasus: Batik Putra Laweyan, Surakarta) - Saqqo, Muhammad Luthfi, Etika Muslimah ST, MM, MT (2017)
Kampoeng batik laweyan is one of sentra craftsman batik who are in surakarta. Sentra craftsman batik from year to year have been improving , even in 2009 turnover entrepreneurs batik rose 50 % .Sentra batik laweyan which was originally 22 units in the 2004 to 51 unit in 2008 .In addition needs raw materials from year to year are high, there should have been strategies to get the raw materials that having good qualities with reachable price .This research using the concept of green productivity (GP), where GP is the concept to increase productivity and lagged environment for economic development in their entirety. Waste reduction done by using the method filtration and methods fitoremediasi to reducing the concentration waste in the three workstations, for his station staining, penglorodan station and station aundering. The following is one of the results of the waste prior to the establishment of waste reduction on station penglorodan known liter 456,2 content Mg/L, cod 858,8 Mg/L, TSS 43,0 Mg/L, pH 7.5 .But after the introduction of waste reduction content was able to reduce waste, the following are the result of waste reduction liter 331,8 Mg/L, cod 721,1 Mg/L, tss 105 Mg/L, pH 7.8. Management of the material that is carried on this research, among other: waste management by means of waste reduction and used of solid waste in the form of wax perca mori and for handicrafts .On the other side management material done by means of successive addition the raw material that is added the raw material of a candle that has been unused to be exploited back. Pollution management conducted by using waste perca mori that has economic values high. In addition, productivity before the management engineering material namely 312% and after the engineering was 329%. The value of the debt could be achieved by do an addition raw materials batik making with other ingredients that has the quality of the same but and affordable.